BAHASA PRANCIS UNTUK PARIWISATA SEBUAH ANALISIS KEBUTUHAN SUBJEKTIF DAN OBJEKTIF MATA KULIAH BAHASA PRANCIS UNTUK MAHASISWA S1 PARIWISATA - Marliza Arsiyana (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2019)
Due to the growing demand of french need in tourism industry and the need for analysing the appropriate materials for Tourism Undergraduate Students in Yogyakarta, the subjective needs and objective analysis are primordial in developing french curriculum. This study is an attempt to analyze subjective and objective language learning needs for tourism undergraduate students of STIPRAM. This study was a qualitative descriptive study using questionnaire method for gathering the data needed. The questionnaire was arranged in multiple–option question pattern. The results of the data analysis revealed there are some differences concerning the theme choices, the belief about the focus of French language learning skills. But there is no difference betwee subjective and objective learning needs of students related to the reason studying french, the importance of french, the future domain of french use and the teaching approach and methode applied in the class.Keywords: Subjective needs, French Course, French for Tourism